Josephus, Judea, and Christian origins: methods and categories - Mason, Steve (Hendrickson Publishers, 2010)
Introduction / by Steve Mason -- Josephus : interpretation and history -- Josephus as authority for first-century Judea -- Of audience and meaning : reading Josephus's Judean War in the context of a Flavian audience -- Figured speech and irony in T. Flavius Josephus -- Contradiction or counterpoint? : Josephus and historical method -- Josephus and Judea -- Jews, Judeans, judaizing, Judaism : problems of categorization in ancient history -- Pharisees in the narratives of Josephus -- The philosophy of Josephus's Pharisees -- The Essenes of Josephus's Judean War : from story to history -- Christian origins -- Paul's announcement : "good news" and its detractors in earliest Christianity -- "For I am not ashamed of the Gospel" (Rom. 1:16) : the Gospel and the first readers of Romans -- Chief priests, Sadducees, Pharisees, and Sanhedrin in Luke-Acts and Josephus